Investigation of the laminar viscous flow in a semi-porous channel in the presence of uniform magnetic field using optimal homotopy asymptotic method - Mohsen Shekholeslami; Hamid Reza Ashorynejad; Davood Doomairry; Ishak Hashim (Universiti Kebangsaan Malaysia, 2012)
In this paper, the problem of laminar viscous flow in a semi-porous channel in the presence of transverse magnetic field is studied. The Optimal Homotopy Asymptotic Method (OHAM) is employed to approximate the solution of the system of nonlinear differential equations governing the problem. The influence of the Hartmann number (Ha) and the Reynolds number (Re) on the flow was investigated. The results of the OHAM were compared with homotopy analysis method (HAM) and variation iteration method (VIM) results.